2020
DOI: 10.1155/2020/3073104
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nose Technologies in Monitoring Black Tea Manufacturing Process

Abstract: “Tea” is a beverage which has a unique taste and aroma. The conventional method of tea manufacturing involves several stages. These are plucking, withering, rolling, fermentation, and finally firing. The quality parameters of tea (color, taste, and aroma) are developed during the fermentation stage where polyphenolic compounds are oxidized when exposed to air. Thus, controlling the fermentation stage will result in more consistent production of quality tea. The level of fermentation is often detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The processing procedures of black tea comprise withering (indoor withering or sun withering), rolling, fermentation, and drying. The unique aroma of black tea is formed during processing . It was reported that fresh tea leaves (Longjing 43) were processed into six tea types by the traditional processing methods, and the formation of tea aroma from these six model manufacturing processes was elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processing procedures of black tea comprise withering (indoor withering or sun withering), rolling, fermentation, and drying. The unique aroma of black tea is formed during processing . It was reported that fresh tea leaves (Longjing 43) were processed into six tea types by the traditional processing methods, and the formation of tea aroma from these six model manufacturing processes was elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The unique aroma of black tea is formed during processing. 27 It was reported that fresh tea leaves (Longjing 43) were processed into six tea types by the traditional processing methods, and the formation of tea aroma from these six model manufacturing processes was elucidated. Feng et al indicated that the MeJA concentration was the highest in the black tea sample among the six tea types.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Innovative technologies were developed by several research groups using the electronic eye method [5,11,[13][14][15][16][17][18], the electronic tongue method [19][20][21][22], and the electronic nose method [23][24][25][26][27][28][29][30][31][32][33][34][35] that aim at minimizing human intervention. At present, the electronic nose methods are often utilized to classify different types of tea or different tea grades [24,26,31,35].…”
Section: Introductionmentioning
confidence: 99%
“…Theaflavin and thearubigin increase a brewed tea's color, mouth-feel and body, and contribute to the briskness of the tea. These compounds are of such importance to the characteristic flavor and aroma of tea that methods of optimizing fermentation levels have been studied [3]. Feng et al (2019) investigated the effect of manufacturing processes on the aroma composition of tea leaves and reported that black tea has a concentration of 710 µg/g of volatile compounds whereas green tea has 20 µg/g [4].…”
Section: Introductionmentioning
confidence: 99%